The principles of stock breeding - Thatcher, Harry Raymond (My University, 1903)
Introduction: The fundamental principles of stock breeding are based on the laws of organic evolution, and one who would attain the highest skill in the art must have a thorough understanding of these laws. He should also have a thorough knowledge of anatomy and animal nutrition. He must have financial backing that will enable him to obtain animals of high economic importance. The selection of these animals and the determination if the resultant forms are developing as desired demands rare judgment. As Chas Darwin aptly says, “Not on man in a thousand has the accuracy of eye or the judgment sufficient to become a great breeder. If gifted with these qualities and he studies his subject for years and devotes a lifetime to it with indomitable perseverance he will succeed and make great improvements, if he lacks any of these qualities he will assuredly fail.” It is thus evident that there are factors which are dependent on the individual breeder and the financial conditions which surround him. But the laws of organic evolution have a bearing on this industrial art under all conditions and in that light let us consider it. First let us briefly restate those laws as formulated by Chas. Darwin (whose works should be carefully studied by every breeder) and his followers. I All plants and animals tend to resemble their parents. II All plants and animals tend to vary from their parents. III All plants and animals tend to increase in a geometrical ratio. IV All plants and animals are influenced by their environment. V All plants and animals must struggle for existence and ultimately the fittest will survive.
Citation: Thatcher, Harry Raymond. The principles of stock breeding. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Louisiana Purchase; Thomas Jefferson; Missouri Compromise; Theses; Manuscripts (documents)